Information mastery skills among pre-clerkship students in a problem-based learning curriculum: a case report. - Duffy, Christopher; Tripp, Tovah; Schneier, Ezra; Dreker, Margaret; Hoffman, Miriam; Josephs, Joshua (Journal of the Medical Library Association, 2026)
Background: Use of evidence-based medicine (EBM) can improve patient outcomes, but translating classroom learning of EBM to clinical practice is challenging. Training students to utilize and apply principles of EBM is critical but data and methods for evaluating students' EBM skills are lacking. Case Presentation: The Hackensack Meridian School of Medicine has early curricular introduction of information mastery techniques to combat these challenges. Students create research presentations related to the weekly problembased- learning (PBL) case to practice applying EBM skills. Medical librarians developed and utilized an assessment tool to evaluate students' weekly presentations. Librarian staff reviewed 595 presentations during the first year of the preclerkship curriculum using five criteria: (1) appropriate scope of presentation (2) correct categorization of the question based on the finding information framework (3) appropriate resource used (4) search strategy and (5) bibliographic citations according to American Medical Association (AMA) guidelines. Conclusions: Of the evaluated presentations using these criteria, the majority of students routinely and reliably applied EBM skills in their case-based presentations. Further studies will need to look at continued development of these skills throughout other phases of training.